A COMPARISON OF VIOLATION PHENOMENA OF COOPERATIVE PRINCIPLE IN TRADITIONAL MARKET PASAR RAYA AND TRADITIONAL MARKET LUBUK ALUNG - Marisa Kurniawan; Havid Ardi (Universitas Negeri Padang, 2019)
The study deals with violating maxims by the sellers and the buyers in traditional markets of Pasar Raya and Lubuk Alung. The objectives of the study are to find out how sellers and buyers do violation maxims in their transactions in traditional market Pasar Raya and Lubuk Alung and to identify the differences and similarities of violation of maxims between traditional market Pasar Raya Padang and Lubuk Alung. This research was conducted by using descriptive qualitative method. The data were the utterances between sellers and buyers from 21 conversations each traditional market. The data were collected by recording the conversations. There were 108 utterances that violated the maxims used by sellers and buyers traditional market Pasar Raya while in traditional market Lubuk Alung there were 106 utterances that violated maxims used by sellers and buyers. The implications of violating maxims that used by sellers and buyers were to show closeness and become the part of their purpose how they do transaction each other, how they attract the customers, and how they get a deal in bargaining transaction.